2015
DOI: 10.1177/1060028015622649
|View full text |Cite
|
Sign up to set email alerts
|

Association of Statin Therapy and Risks of Cholelithiasis, Biliary Tract Diseases, and Gallbladder Procedures

Abstract: Statin use was not significantly associated with either an increased or decreased risk of cholelithiasis or gallbladder disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The study methods have been previously published . Briefly, this was a retrospective cohort study using patients enrolled in the San Antonio Military Healthcare System from October 1, 2003, to March 1, 2012, after approval from institutional review boards of relevant institutions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study methods have been previously published . Briefly, this was a retrospective cohort study using patients enrolled in the San Antonio Military Healthcare System from October 1, 2003, to March 1, 2012, after approval from institutional review boards of relevant institutions.…”
Section: Methodsmentioning
confidence: 99%
“…Statin therapy was not limited to any particular statin or dose. Exclusion criteria included those who received statins for <90 days during the study period or were initiated on statins after the baseline period …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been reported that statin therapy, which is taken as a class of most effective drugs for lipid-lower therapy, is not significantly associated with either an increased or decreased risk of gallstone. 35 Therefore, statins may not be effective to reverse hypercholesterolemia-induced changes in gallstone formation. In the present study, we found that hypercholesterolemia reduced Tyr-phosphorylation of BK Ca a-subunit, which may play a key role in downregulated BK Ca channel activity and SO motility.…”
mentioning
confidence: 99%